Imaging in pediatric renal transplantation. (25th January 2017) - Damasio, Maria Beatrice; Ording Muller, Lil‐Sofie; Piaggio, Giorgio; Marks, Stephen D.; Riccabona, Michael
Abstract: Renal transplantation is the therapy of choice in children with ESKD. Radiological investigations are required in both pre‐ and post‐transplant assessment, although there is paucity of both consensus‐based statements and evidence‐based imaging guidelines in pediatric renal transplantation. The phases of pediatric ESKD management that require imaging are pretransplantation recipient assessment and post‐transplantation surveillance for detection of potential complications. We present suggestions for imaging algorithms for both pre‐ and post‐transplant assessment in pediatric renal transplant recipients.